2011
DOI: 10.1021/ja200559j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity of Gold-Supported Cobalt Oxide for the Electrochemical Evolution of Oxygen

Abstract: Scanning electron microscopy, linear sweep voltammetry, chronoamperometry, and in situ surface-enhanced Raman spectroscopy were used to investigate the electrochemical oxygen evolution reaction (OER) occurring on cobalt oxide films deposited on Au and other metal substrates. All experiments were carried out in 0.1 M KOH. A remarkable finding is that the turnover frequency for the OER exhibited by ∼0.4 ML of cobalt oxide deposited on Au is 40 times higher than that of bulk cobalt oxide. The activity of small am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
1,187
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,323 publications
(1,293 citation statements)
references
References 50 publications
93
1,187
12
1
Order By: Relevance
“…Yeo et al examined this by depositing Co 3 O 4 on Au as well as other metallic substrates. It was found that the OER activity of Au‐supported Co 3 O 4 was 40 times higher than its bulk counterpart, whereas Co 3 O 4 with other metal substrates exhibited less significant enhancement 143. The OER activity of Co 3 O 4 increased with the increasing electronegativity of metal substrates in a sequence of Au > Pt > Pd > Cu > Co.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…Yeo et al examined this by depositing Co 3 O 4 on Au as well as other metallic substrates. It was found that the OER activity of Au‐supported Co 3 O 4 was 40 times higher than its bulk counterpart, whereas Co 3 O 4 with other metal substrates exhibited less significant enhancement 143. The OER activity of Co 3 O 4 increased with the increasing electronegativity of metal substrates in a sequence of Au > Pt > Pd > Cu > Co.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…They found that the lowest OER onset potential was obtained for a manganese oxide modified Au substrate. In a number of recent publications, Bell and coworkers 25,27 have also highlighted the effect of the substrate on the electrocatalytic properties of Ni and Co oxides. In particular, they observed that the OER activity of a submonolayer of cobalt oxide decreases in the order CoO x /Au > CoO x /Pt > CoO x /Pd > CoO x / Cu > CoO x /Co.…”
Section: Bulk Oxide/hydroxide Electrodesmentioning
confidence: 99%
“…In particular, they observed that the OER activity of a submonolayer of cobalt oxide decreases in the order CoO x /Au > CoO x /Pt > CoO x /Pd > CoO x / Cu > CoO x /Co. 27 This trend was interpreted in terms of the electronegativities of the substrates. That is, the more electronegative metals, such as Au, can facilitate the formation of higher Co oxidation states thereby improving the electrocatalytic properties of the oxide.…”
Section: Bulk Oxide/hydroxide Electrodesmentioning
confidence: 99%
See 2 more Smart Citations